Comparative efficacy of holmium laser versus plasma techniques in the surgical management of non-muscle invasive bladder cancer: a meta-analysis - Li, Dong; Xu, Jia-Neng; Chen, Han-Kai; Ren, Qiang; Li, Yu-Min (Frontiers in Oncology, 2025)
BackgroundThis systematic review and meta-analysis compared the efficacy of Holmium Laser and Plasma Techniques in treating non-muscle invasive bladder cancer (NMIBC), focusing on surgical duration, safety, and tumor recurrence.MethodsAdhering to PRISMA guidelines, we included randomized controlled trials that directly compared Holmium Laser and Plasma Techniques in NMIBC treatment. The Cochrane Collaboration’s tool assessed study quality, and statistical analyses were conducted using fixed-effect or random-effects models based on heterogeneity. Sensitivity analyses and publication bias assessments were also performed.ResultsOur search yielded 1158 potentially relevant articles, with 8 studies meeting our inclusion criteria. The analysis showed no significant difference in surgical duration between the two techniques. However, the Holmium Laser was associated with a significantly lower incidence of intraoperative bladder perforation (RR=0.10, P<0.001) and a reduced short-term tumor recurrence rate (RR=0.65, P<0.01). Sensitivity analysis confirmed the robustness of these findings, and no significant publication bias was detected.ConclusionsHolmium Laser provides safer outcomes and better efficacy in reducing postoperative tumor recurrence compared to Plasma Techniques in NMIBC management.